Power and politics in different change discourses - Guido Maes; Geert Van Hootegem (Administrative Sciences, 2022)
Background: The purpose of this article is to examine how different views on power and politics manifest in organizational change, and how they can be integrated into a single model. Methods: Our research was based on an extensive literature review about power and politics and their relationship with organizational change. We used the systems model of organizational change developed by Maes and Van Hootegem to map the different views on power and politics in organizational change. This systems model integrated different change discourses and allowed us to post the various aspects of power and politics in organizational change. Results: Using the systems model as a reference to look at power and politics from different angles led to a better understanding of the role they play in organizational change so that actors can enter the political arena of change better prepared and play the game of change at a tactically higher level. Conclusions: The analysis contributes to the study of power and politics in three respects. First, using the metamodel of organizational change to map the different views on power and politics offers a more detailed and varied understanding of the use of power and politics in organizational change. Second, looking at power and politics from different discourses can accommodate greater complexity and nuance. Third, it shows that change projects rarely run smoothly but are constantly traversed by all kinds of obstacles and barriers that require specific political astuteness. Members of an organization, who have been introduced to political skills, will be better able to navigate the pitfalls of organizational change and its rhetoric and thus be better agents of change or better able to resist unreasonable change.
Keywords: 350; power; politics; change management; discourse; system model